Autophagy Is a Potential Therapeutic Target Against Duck Tembusu Virus Infection in vivo - Hu, Zhiqiang; Pan, Yuhong; Cheng, Anchun; Zhang, Xingcui; Wang, Mingshu; Chen, Shun; Zhu, Dekang; Liu, Mafeng; Yang, Qiao; Wu, Ying; Zhao, Xinxin; Huang, Juan; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Duck tembusu virus (DTMUV) is newly emerged in poultry and causes great losses to the breeding industry in China and neighboring countries. Effective antiviral strategies are still being studied. Autophagy is a cellular degradative pathway, and our lab's previous data show that autophagy promotes DTMUV replication in vitro. To study the role of autophagy further in vivo, we utilized ducks as the animal model to investigate the autophagy responses in DTMUV-targeted tissues. And also, we utilized autophagy regulators, including Rapamycin (Rapa) as the autophagy enhancer, 3-Methyladenine (3-MA) and Chloroquine (CQ) as the autophagy inhibitors, to adjust the host autophagic levels and then study the effects of autophagy on tissue damages and virus replication. As a result, we first found DTMUV infection trigged autophagy and autophagy regulator treatments regulated autophagy levels successfully in duck spleens and brains. Next, we found that autophagy inhibitors inhibited DTMUV replication and alleviated DTMUV-induced pathological symptoms, whereas the autophagy inducer treatment led to the opposite effects. And we also found that autophagic regulation was correlated with the expression of innate immune genes, including pattern recognition receptors, type I interferons, and cytokines, and caused different effects in different tissues. In summary, we demonstrated that autophagy facilitated DTMUV replication, aggravated the developments of pathological symptoms and possibly counteracts the host's innate immunity response in vivo.